Colour Stability of Veneering Composites after Accelerated Aging - Papadopoulos, Triantafillos; Sarafianou, Aspasia; Hatzikyriakos, Andreas (European Journal of Dentistry, 2010)
Objectives: To investigate the colour stability of four indirect composite restorative materials after accelerated aging.Methods: Four indirect composites (Gradia, Signum+, HFO and Adoro) were used. For each material, six specimens were prepared and subjected to accelerated aging (Suntest CPS+, Atlas, Chicago, IL, USA) according to ISO 7491. A Dr. Lange Microcolor Data Station colorimeter (Braive Instruments, Liege, Belgium) was used to measure specimen colour before and after aging. Measurements were performed according to the CIE L*a*b* system, and the mean L*, a* and b* values for each material were calculated. The equation ΔΕ = [(ΔL*)2 + (Δa*)2 + (Δb*)2]1/2 was used to measure the total colour change (ΔΕ), where ΔL*, Δa* and Δb* are the differences in the respective values before and after aging. One-way ANOVA were used to determine statistically significant differences in ΔL*, Δa*, Δb* and ΔΕ.Results: No statistically significant differences were found in ΔL*, Δa*, Δb* and ΔΕ among the materials tested (PΔL*=.063; PΔa*=.521; PΔb*=.984 and PΔE=.408). After aging, Gradia specimens showed an increase in lightness (ΔL*=0.36) and a green-yellow shift (Δa*=-1.18, Δb*=0.6), while Signum+ specimens exhibited an increase in lightness (ΔL*=0.5) and a green-blue shift (Δa*=-0.9, Δb*=- 0.45). HFO specimens exhibited an increase in lightness (ΔL*=0.75) and a green-yellow shift (Δa*=- 1.3, Δb*=0.06), and Adoro specimens exhibited an increase in lightness (ΔL*=2.07) and a green-yellow shift (Δa*=-1.3, Δb*=0.68).Conclusions: Colour changes were found to be within accepted values of perceptibility and clinical acceptance after accelerated aging, and no statistically significant differences were found in ΔL*, Δa*, Δb* and ΔΕ among the materials tested. (Eur J Dent 2010;4:137-142)
Keywords: Colour stability; Indirect composites; Accelerated aging